The missile defense equation factors for decision making - Mantle, Peter J. (American Institute of Aeronautics and Astronautics, 2004)
The author, a former U.S. Navy program manager and Pentagon insider, has written this book to help decision makers sort out the costs and technical merits of competing missile defense technologies now in development or under research. The book is targeted not just to executive decision makers, but also anyone in the missile-defense decision chain